SELEKTIVITAS ALAT TANGKAP RAJUNGAN (Portunus pelagicus) DI PERAIRAN SEGERI KABUPATEN PANGKEP - Muhammad Jamal; Hasrun Hasrun; Ihsan Ihsan; Ernaningsih Ernaningsih (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The research aims to determine the size distribution of crabs caught, determine the proportion of swimming crabs that are suitable for catching and analyze the selectivity of gillnet and dragon trap fishing gear. This research will be carried out from May - December 2023 in the Bawasalo area, Segeri District, Pangkep Regency The parameters calculated for determining size distribution use a distribution table based on Sturgess, the proportion of size suitable for catching using the Odum rule and the selectivity of gill net crab and dragon fish traps using the Sparre and Venema rule. The research results showed that (1) the size structure of crab carapace caught with gillnet fishing gear was dominant in the range of 10.1-11.0 cm with a frequency of 202 individuals, then the size structure of crab carapace caught with gillnet fishing gear was dominant in the range of 9.1 -10.0 cm with a frequency of 278 individuals, while the carapace size structure of male crabs is dominant in the range of 9.1-10.0 cm with a frequency of 289 individuals and the carapace size structure of female crabs is dominant at 10.1-11.0 cm with a frequency of 184 fish, (2) The value of allowable catch size (ACS) of crabs caughtb by gillnets is 66.9% and those not allowable catch size (nACS) is 33.1% 920 while the ACS size value of crabs caught by fish traps is 39.6% and the BLT size is 60.4%. The LT size value of male crab is 50.5% and the nACS is 39.5% and the ACS size value of female crab is 56.8 and the nACS is 43.2% (3, Fishing gear gillnet has a higher selectivity value compared to dragon traps.